2020
DOI: 10.1016/j.anyes.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Traducción al español y validación de una medida breve de ansiedad por la COVID-19 en estudiantes de ciencias de la salud

Abstract: Introducción y Objetivos: El COVID-19 ha generado consecuencias negativas para la salud mental de las personas. Este es el caso del Perú, uno de los países latinoamericanos más afectados por la pandemia. En este sentido, el objetivo del estudio fue traducir y validar la Coronavirus Anxiety Scale (CAS) al español. Material y Método: Los participantes fueron 704 estudiantes universitarios de ciencias de la salud (Medad = 23.39 años, DE = 3.45) a quienes se les administró el CAS en español, el Mental H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
19
0
10
Order By: Relevance
“…The CAS has 5 items with 5 Likert type options (0 ¼ nothing to 4 ¼ almost every day during the last 2 weeks), where a higher score expresses a greater anxiety in front of the COVID-19. The version translated into Spanish and validated in the Peruvian context by Caycho-Rodr ıguez, Barboza-Palomino, et al (2020) was used, which has adequate evidence of construct validity, evidence of validity based on the relationship with other variables, and reliability.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CAS has 5 items with 5 Likert type options (0 ¼ nothing to 4 ¼ almost every day during the last 2 weeks), where a higher score expresses a greater anxiety in front of the COVID-19. The version translated into Spanish and validated in the Peruvian context by Caycho-Rodr ıguez, Barboza-Palomino, et al (2020) was used, which has adequate evidence of construct validity, evidence of validity based on the relationship with other variables, and reliability.…”
Section: Instrumentsmentioning
confidence: 99%
“…The CAS was originally developed in English and its psychometric properties were evaluated in that language (Lee, 2020a(Lee, , 2020bLee, Jobe, Mathis, et al, 2020, Lee, Mathis, Jobe, et al, 2020, as well as in Turkish (Evren et al, 2020), Bangla (Ahmed et al, 2020), Korean (Choi et al, 2020) and Spanish (Caycho-Rodr ıguez, Barboza-Palomino, et al, 2020;Franco-Jimenez, 2020;Mora-Magaña et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En estudio experimental de un programa disminuyeron significativamente los valores de cortisol en el cabello para el estado de ansiedad, así como aquellos rasgos en aquellos participantes que completaron el programa, resultó efectivo para disminuir el nivel de estrés y ansiedad en los participantes, ayudando a mejorar la calidad de vida de los estudiantes y los profesionales docentes y no docentes que participaron (Iglesias et al, 2018). Las investigaciones sobre ansiedad siguen siendo vigentes, la versión en español del CAS posee evidencias de validez y confiabilidad para medir la ansiedad por el COVID-19 en una muestra de universitarios (Caycho-Rodríguez et al, 2020).…”
Section: Introductionunclassified
“…Recently, the World Health Organization has indicated that the epicenter of the contagion is in Latin America [Kirby 2020] and, therefore, it is not known how it could affect the course of the disease evolution or how mitigation measures would be carried out, but, in any case, a significant impact on mental health is estimated [Caycho-Rodríguez et al 2020]. In addition, it should be considered that several countries in the region have taken a number of very rigid and highly anticipated measures of strict quarantine, which also implies variability in terms of psychosocial involvement.…”
Section: Introductionmentioning
confidence: 99%